Upaya Hukum Perlawanan Pihak Ketiga ( Derden Verzet ) terhadap Putusan Pengadilan yang Berkekuatan Hukum Tetap dalam Perkara Perdata - Bendesa Made Cintia Buana (JURNAL RECHTENS, 2014)
In any civil activity always bore legal consequences for the parties concerned. But there are times when the parties are not able to carry out the legal consequences. So that there arises a civil case that later settled in the district court where the legal events that occurred. Starting from the existence of a lawsuit filed by the plaintiff, then the plaintiff and defendant mutually upfront faced trial. From this civil proceedings conducted until the final stage of the court decision.